Helium diffraction and acoustic phonons of graphene grown on copper foil. (December 2015) - Al Taleb, Amjad; Yu, Hak Ki; Anemone, Gloria; Farías, Daniel; Wodtke, Alec M.
Abstract: We report helium diffraction from graphene grown by chemical vapour deposition (CVD) using copper foil. This method reveals acoustic phonons, which are physically important to thermal conductance as well as a sensitive probe of graphene's interactions with the underlying substrate. Helium diffraction is made possible by the high quality of graphene produced by a recently reported "peel-off method". The graphene lattice parameter was found to remain constant in the temperature range between 110 and 500 K. The measured parabolic dispersion of the flexural mode along Γ ¯ M ¯ allows determining the bending rigidity k = (1.30 ± 0.15) eV, and the graphene–Cu coupling strength g = (5.7 ± 0.4) × 10 19 N/m 3 . Unlike analytics employing atomic resolution microscopy, we obtain information on the atomic-scale quality of the graphene over mm length scales, suggesting the potential for Helium atom scattering to become an important tool for controlling the quality of industrially produced graphene.